2022
DOI: 10.3390/ijms231911966
|View full text |Cite
|
Sign up to set email alerts
|

Effective Modulation by Lacosamide on Cumulative Inhibition of INa during High-Frequency Stimulation and Recovery of INa Block during Conditioning Pulse Train

Abstract: The effects of lacosamide (LCS, Vimpat®), an anti-convulsant and analgesic, on voltage-gated Na+ current (INa) were investigated. LCS suppressed both the peak (transient, INa(T)) and sustained (late, INa(L)) components of INa with the IC50 values of 78 and 34 μM found in GH3 cells and of 112 and 26 μM in Neuro-2a cells, respectively. In GH3 cells, the voltage-dependent hysteresis of persistent INa (INa(P)) during the triangular ramp pulse was strikingly attenuated, and the decaying time constant (τ) of INa(T) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…However, because of the multiple therapeutic effects of this drug, additional electrophysiological actions need to be further explored. A recent report by Wu et al [ 3 ] demonstrated that I Na(T) and I Na(L) were differentially suppressed with IC 50 values of 112 and 26 μM, respectively. The hysteretic strength of persistent I Na in response to a triangular ramp pulse was inhibited by LCS exposure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the multiple therapeutic effects of this drug, additional electrophysiological actions need to be further explored. A recent report by Wu et al [ 3 ] demonstrated that I Na(T) and I Na(L) were differentially suppressed with IC 50 values of 112 and 26 μM, respectively. The hysteretic strength of persistent I Na in response to a triangular ramp pulse was inhibited by LCS exposure.…”
mentioning
confidence: 99%
“…Moreover, the fast and slow time constants of recovery from the I Na block by the conditioning pulse-train depolarization were increased. Therefore, the results disclosed that LCS could interact with voltage-gated sodium (Na V ) channels to alter the magnitude, gating, frequency dependence, and voltage-dependent hysteresis of I Na in excitable cells [ 3 ].…”
mentioning
confidence: 99%